The Dynamics of the Balinese Literature in the Present Day Bali - I Ketut Ardhana (Pusat Kajian Bali Universitas Udayana, 2014)
AbstractBalinese literature has a significant role in the context of how the Balinese have preserved their own cultural tradition up to now. Even though the Majapahit Kingdom in the fourteenth century strongly influenced the Balinese tradition in the past, but itseems that the Balinese recently also look back at their cultural tradition prior to the period of the Majapahit influence. There are some crucial issues in relation to the above explanation: firstly,there have been widely debated on the issue around the originof the Balinese tradition. On the one hand scholars argue thatthe origin of Balinese tradition is not started from the East Java period, but it was earlier than that it had been started prior to the period of the Majapahit such as the Middle Java period inthe 8th to 9th century or, even, in the West Java Hindu tradition that also played a major role. However, others have not convinced with this argument; Secondly; due to globalization process, theBalinese perceive that the only way to anticipate the impacts of globalization is just to revitalize the local Balinese cultures by seeking at the Balinese literatures as the local sources like the babad, paswara, and awig-awig; Thirdly; to counter the negative impacts of globalization, the Balinese use their local cultural heritage so that they can maintain their cultural tradition that not based on Balinese tradition, but also the Javanese tradition. Itis important to discuss such issue since the influences of pre and post Majapahit cultural traditions have indeed influenced thecultural identity of the Balinese. On top of this, to understand the concept of multiculturalism in the present day Bali, one needs to trace back the dynamic of interplay amongst arrays of cultural traditions that have affected the origin of multicultural society there.